Technical developments in transurethral resection of bladder tumours - Pastuszak, Agata; Zdrojowy, Romuald; Poletajew, Sławomir; Adamowicz, Jan; Krajewski, Wojciech (Contemporary Oncology/Współczesna Onkologia, 2019)
Bladder cancer is one of the most common malignancies worldwide. The transurethral resection of bladder tumour (TURB) remains the gold standard in both diagnostics and treatment. Because of the importance of TURB in bladder cancer management and the fact that TURB is one of the most commonly performed urologic procedures, it is the subject of continuous technological development. The latest advances in the field of endourology are aimed at increasing surgical accuracy and thus reducing the risk of bladder tumour recurrence and progression. However, despite the constant progress in technology and technique, there are still a lack of good quality data showing the superiority of any of the methods. The aim of this paper is to present available data on new technological developments in surgical technique of TURB. Advantages and disadvantages of currently available methods are discussed, and literature showing their effectiveness and safety is shown.